How Indonesian EFL learners perceive error corrections - Suatmo Pantja Putra; Hairus Salikin (Universitas Merdeka Malang, 2020)
This study aims to obtain an in-depth understanding of error corrections in speaking from learners’ perspectives due to the fact that error corrections are often provided without considering the learners’ point of view. Although the results of the research discussing effectiveness of error corrections in speaking remain unclear, especially in an English as Foreign Language (EFL) setting, they naturally exist particularly in the process of learning and teaching EFL. To examine the EFL learners’ perceptions on corrections in speaking, nine EFL students were interviewed the effect of applying snowball sampling technique. The study meets the characteristics of qualitative research. The focus of the study is spoken error corrections, which naturally exist in an instructed Foreign Language learning situation and the researcher is the key instrument in that the researcher asks questions and interacts with the research subjects. The results of the interviews, which are audio recorded and transcribed, are analyzed to develop a descriptive model that encompasses all cases of the phenomena. The findings reveal that mispronunciation, grammatical errors, and lexical errors are important to be taken into account. DOI: 10.26905/enjourme.v4i2.4274